Long‐term safety outcome of systemic immunosuppression in pig‐to‐nonhuman primate corneal xenotransplantation. (18th August 2018) - Choi, Se Hyun; Yoon, Chang Ho; Lee, Hyun Ju; Kim, Hong Pyo; Kim, Jong Min; Che, Jeong‐Hwan; Roh, Kyoung Min; Choi, Hyuk Jin; Kim, Jiyeon; Hwang, Eung Soo; Park, Chung‐Gyu; Kim, Mee Kum
Abstract: Background: Safety concerns exist for corneal recipients under immunosuppression. We report long‐term safety results of porcine corneal xenotransplantation under immunosuppression in nonhuman primates. Methods: Systemic monitoring data from 49 Chinese rhesus macaques that received pig corneal transplant between 2009 and 2018 were retrospectively reviewed. The recipients were divided into 4 groups depending on the systemic immunosuppressants used: (a) conventional steroid group; costimulation blockade groups ([b] anti‐CD154 antibody, [c] anti‐CD40 antibody); and (d) commercially available immunosuppressants (anti‐CD20 antibody, tacrolimus, basiliximab) group. We compared results of general condition monitoring; hematologic, biochemical, and electrolyte tests; and Rhesus Cytomegalovirus infection monitoring. Results: All recipients recovered from early weight loss. White blood cell counts significantly decreased at 6 months in the steroid and anti‐CD154 groups. Abnormal liver and kidney function and electrolyte imbalance were not observed in all groups. The mean value of Rhesus Cytomegalovirus DNA copies was consistently lower than 200 copies/mL, and antibody titers did not change over time in all groups. Tacrolimus‐associated thrombotic microangiopathy was developed in one case, which resolved after discontinuation of tacrolimus. In 2017, a simian varicella virus outbreak led to clinical signs in 5 that received immunosuppressive therapies, of which 3 died. Conclusion: Costimulatory blockade‐based and anti‐CD20 antibody/tacrolimus‐based immunosuppressive therapies seem to be comparably safe with steroid therapy in nonhuman primates receiving corneal xenotransplantation, as they did not reactivate Rhesus Cytomegalovirus and maintained manageable systemic status. Although reactivation is rare, antiviral prophylaxis for simian varicella virus should be considered in immunocompromised hosts.